Comparing the Impact of Primary Care Practice Design in Two Inner City UK Homelessness Services - Martina Zeitler; Andrea E. Williamson; John Budd; Ruth Spencer; Anton Queen; Richard Lowrie (SAGE Publishing, 2020)
Background: Specialist homeless primary health care services in the United Kingdom have arisen from the need for bespoke approaches to providing health care for people experiencing homelessness but descriptions of the design characteristics of homeless health services together with associated long-term condition (LTC) prevalence, health care utilization, and prescribing remain unexplored, thereby limiting our understanding of potential impact of service configuration on outcomes. Aim: Description of specialist homeless general practitioner services in Glasgow and Edinburgh, in terms of practice design (staff, skill mix, practice systems of registration, and follow-up); and exploration of the potential impact of differences on LTC prevalence, health care utilization, and prescribing. Method: Patient data were collected from computerized general practitioner records in Glasgow (2015, n = 133) and Edinburgh (2016, n = 150). Homeless health service configuration and anonymized patient data, including demographics, LTCs service utilization, and prescribing were summarized and compared. Results: Marked differences in infrastructure emerged between 2 practices, including the patient registration process, segmentation versus integration of services, recording systems, and the availability of staff expertise. Patient characteristics differed in terms of LTC diagnoses, health care utilization and prescribing. Higher rates of recorded mental health and addiction problems were found in Edinburgh, as well as higher rates of physical LTCs, for example, cardiovascular and respiratory conditions. There were significantly higher rates of consultations with nurses and other staff in Edinburgh, although more patients had consultations with pharmacists in Glasgow. Medication adherence was low in both cohorts, and attendance at referral appointments was particularly poor in Glasgow. Conclusion: Service design and professional skill mix influence recording of LTCs, service uptake, and identification and management of health conditions. Service configuration, professional skill mix, and resources may profoundly affect diagnoses, utilization of health care, and prescribing. Attention to homeless service design is important when providing care to this disadvantaged patient group.